Future economics and EFL policy in Saudi Arabia: A systematic review of language planning’s role in digital economy transformation - Ismail, Sayed M.; Namaziandost, Ehsan (Research Journal in Advanced Humanities, 2025)
The present study addresses a thorough analysis of the pivotal relationship among English as a Foreign Language (EFL) policy, economic transformation, and sustainable development within the framework of Saudi Arabia's Vision 2030 reform initiative. As the Kingdom hastens its transition to a knowledge-based digital economy, language planning—especially EFL education—becomes a crucial element in enabling this socio-economic transformation. This study conducts a systematic review of peer-reviewed literature, government policy documents, and international reports from 2015 to 2023 to examine how strategic alignment of EFL policy can facilitate the attainment of two primary Sustainable Development Goals: SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth). The analysis identifies three principal mechanisms by which EFL policy advances national development goals: (1) enhancing digital literacy among Saudi youth to align with the requirements of the emerging technology sectors, (2) enhancing workforce competitiveness in globalized markets, and (3) promoting international collaboration in research and innovation. The present delineates existing deficiencies in Saudi Arabia's EFL curriculum, specifically highlighting the necessity for enhanced focus on English for Specific Purposes (ESP) across STEM disciplines, and offers evidence-based suggestions for policy change. This includes the incorporation of industry-relevant language skills into higher education curricula, the establishment of public-private collaborations for language enhancement projects, and the execution of educator training programs centered on contemporary pedagogical methods. Findings indicate that when EFL policy is well implemented, it not only facilitates human capital development but also acts as a catalyst for sustainable economic diversification, a fundamental component of Vision 2030. This study enhances academic and policy discourse by offering a paradigm that conceptualizes language education as a strategic investment in national development, rather than only an academic subject.